Serum and salivary adipokines in type 2 diabetes – Results of a pilot study in India. Issue 7 (July 2022) - Vinitha, Ramachandran; Yogalakshmi, Raghuraman; Rajeswari, Anandhan; Snehalatha, Chamukuttan; Nair, Dhruv Rajesh; Susairaj, Priscilla; Satheesh, Krishnamoorthy; Nanditha, Arun; Raghavan, Arun; Arun, K.V.; Ramachandran, Ambady
Abstract: Background and aims: Association of serum and salivary adiponectin, apelin, visfatin and vaspin were studied in type 2 diabetes (T2DM) among Asian Indians. Their concentrations in periodontitis were also studied. Methods: In this cross-sectional analysis, men and women aged ≥35 years, with no history of diabetes, were screened for ≥3 risk factors for T2DM (n = 615). Eligible persons underwent a 75 gm oral glucose tolerance test and were categorized as Group A (Normal and Impaired Glucose Tolerant, n = 65) and Group B (Incident T2DM, n = 25). Screening for periodontitis was done. Saliva samples were collected in the morning. Participants refrained from food intake for about 2 hours prior to collection . Serum and saliva were stored for analysis. Results: Serum adiponectin was low (p = 0.006) in T2DM and correlated with its salivary levels (r = 0.46, p < 0.001). Serum apelin levels were similar, but salivary concentrations were higher (p = 0.014) in T2DM. Higher serum (p = 0.016) and salivary (p = 0.03) visfatin levels were seen in T2DM. Vaspin levels showed no significant difference in the two groups, either in blood or saliva. Serum adipokines did not differ in the presence of periodontitis. In saliva, higher vaspin (p = 0.034) and lower visfatin (p = 0.018) concentrations were observed. Conclusions: The selected adipokines were measurable in saliva, in lower concentrations. Salivary adiponectin and visfatin measurements may be useful in studies on T2DM. Highlights: Adiponectin, apelin, visfatin and vaspin were measurable in saliva. Salivary adiponectin was low in type 2 diabetes and mirrored its serum levels. Higher serum and salivary visfatin levels were associated with type 2 diabetes. Salivary adiponectin and visfatin measurements may be potential markers of type 2 diabetes.